Morphometric Approach to Angiogenesis In Acute Leukemia: An Attempt to Bring Objectivity - Verma, Shipra; Mutreja, Deepti; Dibyajyoti, Boruah; S, Venkatesan (Annals of Pathology and Laboratory Medicine, 2022)
Background:Angiogenesis is central to growth and development of all tissues, whether they are healthy or diseased. Angiogenesis has a key role in progression of tumor and in its metastasis and invasion. The role of angiogenesis in solid tumors is well established through various studies, but the same needs to be studied more extensively with respect to hematological malignancies. This could aid in prognostication and has therapeutic implications. The aim of the present study was to evaluate bone marrow microvessels in cases of acute leukemias by morphometry, for the purpose of providing objectivity, and study the angiogenic activity in these cases. Methods:In this study, all retrospective and prospective cases of acute leukemias diagnosed on bone marrow biopsies over a period of two years, from 2018 to 2020, were included. A total of 46 cases and 27 controls were studied. Hematoxylin and Eosin (H&E) and CD34 stained bone marrow biopsies were reviewed. For quantification of microvessel density (MVD), three â€œhotspotsâ€ (areas with maximum number of microvessels) on bone marrow biopsy were identified by scanning at x100 power. Then, at x400 magnification, the field was set to cover the maximum number of microvessels within the hotspot, and microvessels were counted in one field in each of the three hotspots. MVD was reported as the mean of the three hotspots expressed as the number of microvessels per mm2. The mean values of the measurements in the three fields were used for statistical analysis. Result: The cases of acute leukemia were found to have significantly higher MVD as compared to the control group. Present study also found significant correlation of MVD with marrow fibrosis and blast percentage in peripheral blood. However, the mean MVD did not show any significant correlation with the bone marrow cellularity. A significant reduction in MVD was found post therapy in the remission cases, while MVD was still high in case with relapse. Conclusion: There is a definite role of angiogenesis in pathophysiology of hematological malignancies. Assessment of bone marrow MVD by morphometry can help in lending objectivity to angiogenesis, which can aid in prognostication and therapeutics in cases of acute leukemias.